Methionine metabolism in human pregnancy(1)(2)(3) - Dasarathy, Jaividhya (American Society for Nutrition, 2010)
Background: Hyperhomocysteinemia during pregnancy, which is a consequence of perturbations in methionine and/or folate metabolism, has been implicated in adverse outcomes such as neural tube defects, preeclampsia, spontaneous abortion, and premature delivery. The adaptive changes in methionine metabolism during pregnancy in humans have not been determined. Objective: Our objective was to examine the kinetics of methionine and its rate of transsulfuration and transmethylation in healthy women with advancing gestation. Design: The whole-body rate of appearance (Ra) of methionine and phenylalanine was measured in healthy pregnant women during the first (n = 10), second (n = 5), and third (n = 10) trimesters of pregnancy. These data were compared with those for nonpregnant women (n = 8). Tracers [1-(13)C]methionine, [C(2)H(3)]methionine, and [(2)H(5)]phenylalanine were administered as prime-constant rate infusions. The effect of enteral high-protein, mixed-nutrient load on tracer-determined variables was also examined. Results: In pregnant women, the Ra of phenylalanine was significantly (P < 0.05) lower in the first trimester than in the second and third trimesters and was significantly lower than that in nonpregnant women. A linear positive correlation was evident between gestational age and phenylalanine Ra. The fractional rate and total rate of transsulfuration of methionine was significantly (P < 0.05) higher during the first trimester, whereas the rate of transmethylation was higher during the third trimester. Plasma concentrations of total cysteine and homocysteine were lower during pregnancy. Conclusions: Uncomplicated pregnancy in humans is associated with a higher rate of transsulfuration early in gestation and a higher rate of transmethylation of methionine in late gestation. These data may have implications for understanding the role of methionine and homocysteine in complications of pregnancy and for the nutritional care of pregnant women.